Experimental investigation on bed shear stress distribution in the roughened compound channel - Akram Abbaspour (Applied Water Science, 2020)
Abstract The roughness in the floodplains in a compound canal and its impact on hydraulic parameters such as the shear stress and their estimation are one of the problems that have attracted the attention of engineers. In this research, the aim is to investigate the effect of artificial on the floodplain of the compound channel on hydraulic parameters. In experiments, slope of channel bed was 0.0015 and three different discharges have been used. The four types of rigid roughness were used to investigate the effect of these parameters. These roughness elements were arranged with zigzag state with two distances of 4 k and 8 k (k is the height of roughness) in the floodplain. A Preston tube with an external diameter of 3 mm that equipped with dynamic pressure sensors was used to compute the shear stress. The Patel calibration curve was used in order to convert the difference between the static and dynamic pressure measured by the Preston tube to the shear stress values. The results showed that for the zigzag arrangement with the density of 4 k, the shear stress is reduced due to the high roughness density and the greater roughened area. In a rough bed, the shear stress in floodplain was significantly higher than smooth bed, and the stress distribution is such that it has descending trend from the main channel toward the wall of the floodplain. The shear stress increase for roughness with a spacing of 8 k is 22–36% higher than the similar hydraulic condition in a smooth bed and the shear stress for condition with the presence of a cylinder with D = 3 cm and roughness spacing of 8 k was 14–18% higher than the shear stress of bed without a cylinder and the same roughness density. The shear stress for condition of the presence of a cylinder with D = 6 cm and roughness spacing of 4 k is 24–30% more than the roughened plain with distances of 4 k.